Uji Kelayakan Air Minum Di Desa Kampung Pinang Kecamatan Perhentian Raja Kabupaten Kampar - Harmiyati Harmiyati; Tessa Shasrini; Sy. Sarah Alwiah; Athasyafa Ramadhan; Gryanda Wahyu Sugeng (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Water is a natural resource that is absolutely necessary for life and human life, as well as in the environmental management system, water is the main element. In everyday life, water is a basic need for the quality and sustainability of human life. Therefore, water must be available in sufficient quantity and quality. Fulfillment of water needs can be done by means of individual systems or communal systems (groups). PAMSIMAS (Community-Based Drinking Water and Sanitation Provision) is one of the programs implemented by the government which is implemented in rural and suburban areas which is carried out with a communal system (https://pamsimas.pu.go.id/). One of them is in Kampung Pinang Village, Perhentian Raja District, Kampar Regency in the form of assistance for clean water tanks. Prior to the existence of the reservoir from the PAMSIMAS government program, villagers used Kampar River water to meet their daily needs. Physically, Kampar river water looks brownish in color, this shows that the water is not suitable for consumption and is used for household needs. The PAMSIMAS that is being built currently uses water sources from below the ground surface which are usually used for cooking needs by the residents of Kampung Pinang Village. However, the water quality physically looks colorful. If this is still used continuously, it will greatly affect the health of the people of Kampung Pinang Village. Clean water is water that meets the requirements for a drinking water supply system, where the intended requirements are requirements in terms of water quality which include physical, chemical, biological and radiological qualities, so that when consumed it does not cause side effects (Kemenkes RI, 1990). From the results of the water quality test from the UPT Health Laboratory of the Pekanbaru City Government Health Service, it was found that for water sourced from PAMSIMAS drilled water, all test parameters met the requirements. Meanwhile, for water originating from rivers, the parameters of turbidity, color, iron, manganese, and total coliforms do not meet the requirements.